Sleep and cognition in aging dogs. A polysomnographic study - Mondino, Alejandra; Catanzariti, Magaly; Mateos, Diego Martin; Khan, Michael; Ludwig, Claire; Kis, Anna; Gruen, Margaret E.; Olby, Natasha J. (Frontiers in Veterinary Science, 2023)
Introduction: Sleep is fundamental for cognitive homeostasis, especially in senior populations since clearance of amyloid beta (key in the pathophysiology of Alzheimer’s disease) occurs during sleep. Some electroencephalographic characteristics of sleep and wakefulness have been considered a hallmark of dementia. Owners of dogs with canine cognitive dysfunction syndrome (a canine analog to Alzheimer’s disease) report that their dogs suffer from difficulty sleeping. The aim of this study was to quantify age-related changes in the sleep-wakefulness cycle macrostructure and electroencephalographic features in senior dogs and to correlate them with their cognitive performance. Methods: We performed polysomnographic recordings in 28 senior dogs during a 2 hour afternoon nap. Percentage of time spent in wakefulness, drowsiness, NREM and REM sleep, as well as latency to the three sleep states were calculated. Spectral power, coherence and Lempel Ziv Complexity of the brain oscillations were estimated. Finally, cognitive performance was evaluated by means of the Canine Dementia Scale Questionnaire and a battery of cognitive tests. Correlations between age, cognitive performance and sleep-wakefulness cycle macrostructure and electroencephalographic features were calculated. Results: Dogs with higher dementia scores and with worse performance in a problem-solving task spent less time in NREM and REM sleep. Additionally, quantitative electroencephalographic analyses showed differences in dogs associated with age or cognitive performance, some of them reflecting shallower sleep in more affected dogs. Discussion: Polysomnographic recordings in dogs can detect sleep-wakefulness cycle changes associated with dementia. Further studies should evaluate its potential clinical use to monitor the progression of canine cognitive dysfunction syndrome.